Merrills' international dispute settlement - Merrills, J. G. (Cambridge University Press, 2022)
"The writing of a new edition of an existing textbook is a challenge, but one that I have gladly accepted and taken on. This seventh edition is rightly entitled 'Merrills' International Dispute Settlement'. In revising the text, I have not only sought to provide an update on the evolutions which had taken place since the last edition, but I have also, and perhaps mostl importantly, tried to maintain and be faithful to the approach adopted by Professor Merrills. It has not been my ambition, for that reason, to completely overhaul the structure and approach adopted in this book, with the risk of otherwise transforming it into a completely new text which would have been too remote from the original intention of Professor Merrills. I have approached the new edition above all as an update and revision of Professor Merrills' work, not my own book on international dispute settlement"--